The Effect of Job Characteristics on Organizational Citizenship Behavior (OCB) with Employee Job Satisfaction as an Intervening Variable in The Banking Sector - Maulidia, Vinda Fidiantika; Rumijati, Aniek; Novianti, Khusnul Rofida (Universitas Muhammadiyah Malang, 2023)
The aim of this research is to determine the influence of job characteristics on organizational citizenship behavior which is mediated by job satisfaction in the banking sector in Malang City, namely PT. Bank Rakyat Indonesia, Kawi Malang Branch. This type of research uses a quantitative approach with a sample of 95 respondents. The source of data obtained in this research was obtained from distributing questionnaires (primary data). Meanwhile, the data analysis technique used in this research uses path analysis. The research results show that job characteristics have a positive and significant effect on organizational citizenship behavior. Job characteristics have a positive and significant effect on employee job satisfaction. Likewise, employee job satisfaction has a positive and significant effect on organizational citizenship behavior. In addition, job satisfaction is proven to mediate the relationship between job characteristics and organizational citizenship behavior.